Bioelectrical Impedance Analysis as a Helpful Tool in Pediatric Obesity Monitoring: A Case Report - Agata Przytula; Joanna Popiolek-Kalisz (Reports)
Background and Clinical Significance: Childhood obesity and its associated complications are an emerging public health problem; thus, non-communicable chronic disease prevention should be implemented as early as possible. On the other hand, obesity management in children is a challenge in terms of achieving fat tissue reduction without any adverse outcomes on overall development. This is why close cooperation with young patients and their parents is crucial for success. Moreover, non-invasive but detailed monitoring guaranties insight in this process’s progress and safety. As obesity is a chronic disease with a tendency for recurrence, further follow-up should also be considered. Case Presentation: We present a case of a 10-year-old boy who was referred to a dietitian due to concerns about a diagnosis of obesity and metabolic complications including abnormal lipid profile and liver function. During the dietary consultation, body composition assessment with bioelectrical impedance analysis was conducted, which confirmed obesity. A detailed interview allowed for the identification of improper dietary patterns. The implemented lifestyle education and qualitative diet modifications led to fat mass reduction without any significant muscle loss after just one month. The metabolic profile was also improved. The patient remained under the care of a dietitian for the next 4 years with constant body composition monitoring, which enabled the relevant parties to address if body mass gain was a part of his normal development or if he suffered from obesity recurrence. The patient and his parents benefited from an individualized, patient-centered approach including dietary education, overall lifestyle modification, and detailed body composition monitoring. This way, the patient succeeded in fat content reduction with the constant assessment of the safety of this process. Moreover, the dietary education impacted the whole family’s lifestyle. Conclusions: This case emphasizes the role of body composition assessment in children. Obesity and metabolic complications resulting from an improper lifestyle can affect pediatric patients. Bioelectrical impedance analysis is a non-invasive tool that can improve the safety and effectiveness of nutritional interventions and could be included in routine pediatric obesity assessment.